2002
DOI: 10.1002/mpo.10168
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial salivary glands neoplasms in children and adolescents: A forty‐four‐year experience

Abstract: Epithelial salivary gland tumors are very rare in children. Surgery is the best option to achieve high cure rates and radiotherapy must have precise indications because of their long-term side effects in young age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
98
2
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 23 publications
18
98
2
8
Order By: Relevance
“…Guzzo et al [27] reported that parotid gland is the main site for pediatric salivary gland tumors (79 %), 71 % of salivary gland tumors are benign, all benign tumors are PA, and the most common malignant tumor is MEC in the pediatric group. In studies by Ribeiro et al [28] and Liu et al [29] very high malignancy rates in pediatric groups were reported: 71 and 54 %, respectively. Shapiro and Bhattacarrya [30] reported that MEC and ACIN-CC consist 43 and 34 % of all pediatric salivary gland malignancies involving major glands.…”
Section: Pediatric Groupmentioning
confidence: 91%
“…Guzzo et al [27] reported that parotid gland is the main site for pediatric salivary gland tumors (79 %), 71 % of salivary gland tumors are benign, all benign tumors are PA, and the most common malignant tumor is MEC in the pediatric group. In studies by Ribeiro et al [28] and Liu et al [29] very high malignancy rates in pediatric groups were reported: 71 and 54 %, respectively. Shapiro and Bhattacarrya [30] reported that MEC and ACIN-CC consist 43 and 34 % of all pediatric salivary gland malignancies involving major glands.…”
Section: Pediatric Groupmentioning
confidence: 91%
“…However, malignant neoplasias were not verified in the first decade of life, while only two cases were diagnosed in the second decade -both of them were mucoepidermoid carcinomas. Studies carried out with children presenting salivary glandular neoplasias and at age below 19 concluded that mucoepidermoid carcinoma was also the most frequent neoplasia found in this age range 6 .…”
Section: Discussionmentioning
confidence: 95%
“…Benign tumors are the most frequent types, corresponding to 54-79% of these diseases, while malignant tumors account for 21-46% of tumors 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The major salivary glands are affected more often, usually represented by the parotid [22][23] . Kolude 24 analyzed 34 MEC patients and found that only 25% of the lesions affected the minor salivary glands, most of which in the palate.…”
Section: Discussionmentioning
confidence: 99%